Integrasi Pendekatan Hermeneutika Dan Sejarah Sebagai Pengembangan Studi Penafsiran Al-Qur’an Di Era Kontemporer - Wely Dozan (Institut Agama Islam Negeri Padangsidimpuan, 2020)
Recently, the discourse in the study of Al-Qur'an exegesis has experienced the development of the epistemology of knowledge and the shift in the paradigm of thinking in science along with the guidance of the times and the various challenges that must be developed. This means that the interpretation of the Al-Qur'an in a broad sense is not implemented as an explanation of the Al-Qur'an text. However, interpretation is an attempt to find solutions and discover the nature and purpose of the Qur'an. This basic assumption gave birth to a handful of theories and a variety of approaches in understanding the text of the Qur'an. The focus of this research, explored several aspects of the study. Among them are, first, tracing the basic concepts of hermeneutic and historical approaches in the development of the al-Qur'an interpretation. Second, tracking applications and contextualization, especially in the field of interpretation. The results of the study show that the hermeneutic and historical approach theory has continuity in interpreting texts. Hermeneutics serves as a contextual understanding of the text with the internationalization chronology and the history of the text both in the old and current situation through a historical approach. Both of these approaches are very important in the application of the contemporary era of the study of al-Qur'an interpretation.